Serbian Orthodox Church, Desecularization and Democracy - Vukomanović, Milan (Poznańskie Studia Slawistyczne, 2016)
In Serbia, in the aftermath of 5 October 2000, the process of desecularization, including the revitalization of the Serbian Orthodox Church (SOC), overlapped with the democratization of its political institutions, as well as with the political and social pluralism. The desecularization of the Serbian society had already started in the socialist Yugoslavia, but the process itself intensified in the early period of political pluralism and establishment of the democratic political institutions. Is Orthodoxy compatible with democracy, viewed not only as the will of the majority or an election procedure, but also as a political culture of pluralism and rule of law? Is Orthodoxy possible as a “civic” church, in line with the European political tradition of democracy and pluralism? The author contends that the contemporary Orthodoxy, including the SOC, accepts globalization in its technical, technological and economic sense, with a parallel tendency towards cultural fragmentation. Thus one needs a consensus between the SOC, state and society in Serbia concerning the basic values, such as: democracy, civil society, pluralistic discourse, secular tolerance and individual human rights.